EFFECTIVE DIGITAL TOOLS FOR ENHANCING ONLINE EDUCATION: TRENDS, APPLICATIONS, AND PEDAGOGICAL IMPACT - Ruhshona Mahmudova (Bright Mind Publishing, 2025)
This article explores the most effective digital tools used in online education, analyzing current trends, practical applications, and their pedagogical impact. The research highlights how innovative technologies such as learning management systems (LMS), interactive platforms, and AI-powered tools enhance student engagement, improve learning outcomes, and support personalized education. Case studies and comparative analyses are provided to demonstrate the effectiveness of these tools in diverse educational contexts. The article also addresses challenges in tool integration and offers recommendations for educators seeking to optimize their online teaching practices.
Keywords: Online education, digital tools, learning management systems, interactive platforms, AI in education, student engagement, pedagogical impact.